The Provision of Local Public Services in a Risky Environment: An Application to Crime - Stefan Traub (Kiel University, Department of Economics, 2006)
We state efficiency conditions for the provision of congestable local public goods that diminish individual-specific proprietary risks. The optimum level of such a public service is determined by equating the sum of the reductions of the expected property losses due to a better service level with the marginal costs of the service. The optimum size of the providing local authority in terms of population is obtained where the increase in proprietary risks due to congestion meets the decrease in contributions for the original citizens. As an empirical example, we employ Germany?s crime statistic in order to assess the efficiency of the provision of police services at the state level.
Keywords: R50; D61; H41; 330; Local Public Goods; Congestion; Risk; Crime; Police; Lokales öffentliches Gut; Polizei; Bottleneck; Risiko; Allokationseffizienz; Schätzung; Theorie; Deutschland